Laboratory Studies Weathered Granites for Excavation Purposes - Kassim, Azman (Faculty of Civil Engineering, 2005)
This research focuses on the most problematic rock type for ripping works in Malaysia particularly weathered sedimentary rocks. The weathering zone that normally requires ripping are zone II-V and these zones has always be problematic zone for excavation in term of selecting the most suitable method and cost evaluation. This research is to examine the relationship of rock material properties and the weathering grades. The information gathered from the monitoring was used for determining the rippability of rocks. Monitored ripping tests were conducted at Bukit Indah which consisted of sandstone and shale. Samples which have been known for their rippability were collected and brought back to the laboratory to determine their parameters for their uniaxial compressive strength test, Brazillian tensile strength, point load test, slake durability and Pundit test. Results from the laboratory tests are presented and their relation with the weathering grade was established. Some of the standard strength tests were not able to test very weak materials with weathering grade V (completely weathered), due to sampling difficulties. By measuring the ripping process, the relationships between the rock properties and the rippability were established. It was revealed that, the laboratory test results alone would not represent the actual behaviour of rock material during rippability assessment. Some of the material found to be weak, are found to be not rippable and vice versa. Thorough field assessments, which need to include discontinuity analysis, are vital and these data are to substantiate the laboratory results.